Model Adaptif Penerjemahan Ihtibak dalam Al-Qur'an: Studi Komparatif atas Al-Qur'an dan Maknanya Karya M. Quraish Shihab dan Terjemahan Kementerian Agama Republik Indonesia - Solihin Bunyamin (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This article examines iḥtibāk as one of the significant rhetorical devices in the Qur’an and its implications for translation into Indonesian. While studies on iḥtibāk have predominantly developed within the fields of classical Arabic rhetoric (balāghah) and Qur’anic exegesis, its relevance to modern Qur’anic translation studies remains relatively underexplored, particularly in the Indonesian context. This study aims to bridge these fields by tracing the development of the concept of iḥtibāk, analyzing the challenges of translating implicit meanings, and conducting a comparative study of two influential Indonesian Qur’an translations: Al-Qur’an dan Maknanya by M. Quraish Shihab and the official translation of the Indonesian Ministry of Religious Affairs. Employing a qualitative library-based methodology with historical, linguistic-rhetorical, and comparative approaches, the study analyzes a corpus of 274 Qur’anic verses identified as containing iḥtibāk in al-Biqā‘ī’s Naẓm al-Durar. The findings demonstrate that iḥtibāk represents a structure of reciprocal omission that requires adaptive translation strategies. Seven adaptive translation models were identified: (1) full explicitation, (2) partial iḥtibāk–tafsīr, (3) semantic expansion, (4) iḥtibāk elimination, (5) tafsīr without iḥtibāk, (6) integrative translation, and (7) contextual-narrative integrative translation. The analysis reveals that Quraish Shihab tends to employ a more adaptive-communicative approach characterized by stronger contextualization and interpretive intervention, whereas the Ministry’s translation adopts a more formal-communicative orientation with selective explicitation. Based on the synthesis of these seven models, this study proposes the concept of adaptive equivalence, a conceptual framework that seeks to balance fidelity to the source text, preservation of rhetorical function, and comprehensibility for target-language readers. The study argues that iḥtibāk should be recognized as an important methodological tool in contemporary Qur’anic translation studies.